Peak Expiratory Flow in Normal Subjects. Issue 5874 (4th August 1973) - Gregg, Ian; Nunn, A. J.
Abstract : The relationship between peak expiratory flow (PEF), age, and height has been studied in 202 men and 199 women in south-west London. Strict criteria of "normality" were employed in the selection of the subjects. Multiple regression techniques were used to determine the form of the relationship for each sex. The findings have been compared with those of other authors, and possible reasons for differences include smoking, residence in a polluted area, and incorrect performance of the test.